PERKEMBANGAN GEOLOGI DAN TEKTONIK PRATERSIER PADA MINTAKAT KUANTAN PEGUNUNGAN DUA BELAS DAN MINTAKAT GUMAI-GARBA, SUMATERA BAGIAN SELATAN - Kusnama Kusnama; Syahrir Andi Mangga (Pusat Survei Geologi, 2007)
The configuration of the pre-Tertiary tectonic and stratigraphic developments of the Southern Sumatera has been an interesting problem for many years. Many geologists have used various concepts in solving the geological problem in order to reconstruct the geological setting of Sumatera and the related surrounding areas.The pre-Tertiary basement in Sumatera comprise allochtonous rocks consisting of many terrains which are composed of various lithologies of different age sand historical backgrounds and they are separated each other by tectonic sutures.The Kuantan-Duabelas Mountain Terrain is occupied by metamorphic, sedimentary and volcanic rocks of Paleozoic-Mesozoic (Carboniferous - Triassic) age and are intruded by the Mesozoic granitoid rocks. The terrain occurred in the western part of Sumatera. Meanwhile, the Gumai-Garba Terrain which is occupied by the tectonite/ melanee, metasediment, carbonate and volcanic rocks of Mesozoic (Jurassic - Cretaceous) age are intruded by the Late Cretaceous granitoid rocks. Keywords: pre-tertiary, tectonic, terrain, Southern Sumatera